Of shepherds, sheep and sheepdogs?: governing the adherent self through complementary and competing ‘pastorates’ - Waring, Justin; Latif, Asam (Sage, 2017)
Foucault’s concept of ‘pastoral power’ describes an important technique for constituting obedient subjects. Derived from his analysis of the Christian pastorate, he saw pastoral power as a prelude to contemporary technologies of governing ‘beyond the State’, where ‘experts’ shepherd self-governing subjects. However, the specific practices of modern pastorate have been little developed. This papers examines the relational practices of pastoral power associated with the government of medicine use within the English healthcare system. The study shows how multiple pastors align their complimentary and variegated practices to conduct behaviours, but also how pastors compete for legitimacy, and face resistance through the mobilisation of alternate discourses and the strategic exploitation of pastoral competition. The paper offers a dynamic view of the modern pastorate within the contemporary assemblages of power.